Narratives of Male Struggle Against Patriarchy in Select Filipino Literary Works - Jhec Aldrei Canibel; Alyssa Amor Gelbolingo; Ma. Cristilina A. Montañez (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This study offers a more nuanced understanding of the impacts of patriarchy by exploring its complexities and effects beyond commonly held beliefs about gender roles. Using an inductive thematic analysis grounded in Braun and Clarke's framework, five Filipino literary works were examined to identify themes related to male struggles within a patriarchal society. The analysis revealed that men who fail to conform to patriarchal norms of masculinity find themselves at odds with the rigid standards of hegemonic masculinity. Their struggles against conformity and the limitations patriarchy imposes extend far beyond personal lives, gradually affecting society at large. These findings suggest that it is imperative for individuals of all genders to unite in collective efforts to dismantle a system that disproportionately privileges only those men narrowly defined as "true." Ultimately, such a system disadvantages those who fail to meet patriarchal standards of masculinity.